Adolescent female disclosure and non-disclosure about their student organization's activities to their parents - Ramos, Jillian Kristin Rodriguez
This descriptive study aims to identify the adolescent females' reasons for joining student organization and to determine adolescent female disclosure and non-disclosure about student organization's activities during the application period to their parents. Interviews and focus group discussions were conducted among 22 adolescent female members of student organizations in the College of Home Economics chosen through snowball sampling. On reasons for joining student organization, 35 % of adolescent females reported sense of belongingness and social life among other reasons namely, security and support, peer influence and curiosity experience. On disclosure to parents, 55 % disclosed to both parents but it was evident that mothers (=45%) received more disclosures than fathers. On reasons for disclosure, 52 % of the responses reported that parents have the "right to know" which suggested that adolescent females chose to disclose to parents out of respect and because they perceive it as a responsibility. Other reasons include parents require the adolescent child to disclose and "parents would listen and understand." On reasons for non-disclosure, 55 % of the responses reported that student organization's activities are trivial among other reasons such as non-inquiry of parents and avoidance of further parental inquiry. Generally, positive and negative feedbacks in the family system were both instigated by disclosure and non-disclosure in the form of parental monitoring and parental support. To have a better picture parent-adolescent child relations, future studies may employ a larger number of respondents to include male respondents, and parents' views on adolescent disclosure and non-disclosure about student organization's activities and use survey and correlational studies.